J.W. Spencer (1851-1921): his Life in Canada, and his Work on Preglacial River Valleys - Middleton, Gerard (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2004)
SUMMARY J.W. Spencer, born and buried in Dundas, Ontario, was a pioneer Canadian geomorphologist. After attending school in Dundas, he moved to Hamilton where he worked in a pharmacy, and was encouraged by local amateur geologists. He attended McGill University from 1871 to 1874, studied under William Dawson and Bernard Harrington, and graduated in the newly reorganized Applied Sciences program. He spent the summer of 1874 working as Robert Bell's assistant in Manitoba, and the following summer working in the Michigan copper mines as an assistant to a mine engineer, Luther Emerson. He obtained a position as science teacher at Hamilton Collegiate Institute (Fig. 1) in 1876. In 1877 he submitted his thesis on Michigan copper deposits to the university at Göttingen, Germany and that summer he visited the university, passed his oral examinations and was awarded the Ph.D., becoming the second Canadian to earn a doctorate in geology. In 1880 he became Professor at King's College, Windsor, Nova Scotia. He concentrated his geological studies on the region around his birthplace at the head of Lake Ontario: at first mainly Paleozoic geology and paleontology, but by 1880 he had switched decisively to surficial geology, particularly the preglacial drainage of Lakes Erie and Ontario. In 1880 he travelled extensively in the United States and attended the AAAS meeting in Boston, where he met J.P. Lesley, who encouraged him to continue his studies of preglacial rivers. In 1882 he accepted a position as Professor and Director of the Museum of Natural History at the University of Missouri.